Is pelvic floor muscle training able to alter the response of cardiovascular autonomic modulation and provide a possible cardiovascular benefit to pregnant women?. Issue 8 (12th August 2020) - da Silva Corrêa, Mikaela; Catai, Aparecida M.; Milan‐Mattos, Juliana C.; Porta, Alberto; Driusso, Patricia
Abstract: Aims: To evaluate the acute and chronic effect of an exercise protocol of pelvic floor muscles (PFMs) contraction on the heart period (HP) and systolic arterial pressure (SAP) variabilities and baroreflex sensitivity (BRS) at rest in pregnant women; and to evaluate if this progressive exercise protocol was well‐tolerated by the pregnant women studied. Methods: We evaluated 48 women at 18 weeks of pregnancy by vaginal palpation, vaginal manometry, and cardiopulmonary exercise test. They were divided in control (CG; 31.75 ± 3.91 years) and training groups (TG; 30.71 ± 3.94 years). At 19 and 36 weeks of pregnancy, electrocardiogram and noninvasive peripheral SAP data were collected at rest before and after 10 PFM contractions. TG performed PFMT from the 20th to the 36th week. HP and SAP variabilities were analyzed by spectral and symbolic analysis. The baroreflex was evaluated by cross‐spectral analysis between the HP and SAP series. Results: The groups did not differ in relation to VO2, HP and SAP variabilities, and BRS at the beginning of the protocol. TG increased the endurance of the PFM after training. PFM contraction did not change the HP and SAP variabilities, and BRS at the 18th week. After the training, the TG presented lower SAP mean, lower BF of SAP variability, and higher BRS than CG. Conclusions: Acute PFM contractions did not alter HP and SAP variabilities and BRS, but PFMT resulted in a lower SAP mean and higher BRS in trained pregnant when compared to the untrained.